(untitled) (Academia Journal of Medicine, 2019)
Background: Dyslipidemia may cause or exacerbate diabetic retinopathy and nephropathy and alterations in the coagulation-fibrnolytic system, changes in membrane permeability, damage to endothelial cells and increased atherosclerosis.Serum triglycerides and all types of lipoproteins are affected and this leads to increase morbidity and mortality in type 2 diabetic patients. Subjects and Methods: A total of 100 with type-2 diabetes mellitus irrespective of duration of diabetes in the age group of 35-80 years formed the study subjects. A pre-structural proforma will be used to collect baseline date detailed clinical history with clinical examination and relevant investigation will be done on participating individuals. Results: During our study we randomly selected 100 Diabetes mellitus-type-2 patients visiting OPD or admitted in the department of Medicine at our institution. Out of 100 DM patients, 61 were Males and 39 were Females. The Mean age of patients in our study was 57.29 +56.55 mg/dl and mean PPBS was 252 +73.76 mg/dl. Conclusion: This study shows significant increasing levels of TG, TC, LDl-C, and Vdl-C and significant decrease in level of HDL-C has the severity of diabetes.